Customers' Switching Barrier on Switching Behavior from Conventional Banks to Sharia Banks - Karim, Kasnaeny; Dani, Ibrahim (Faculty of Economics and Business, Hasanuddin University, 2020)
This study aims to explore the reasons why conventional bank customers have not yet shifted to Islamic (sharia) banking in South Sulawesi, as well as identify the obstacles that have caused customers to remain conventional banks. The research subjects numbered 110 people. The research method uses Mixed Methods with sequential exploratory design. The first stage is a qualitative method to obtain data that is variable because the community has not yet switched to sharia banking. The second stage of the quantitative method is using Factor Analysis, to deepen the data and test the data so that the findings can be generalized. Data were collected by open and closed questionnaires and interviews, validity and reliability tests were carried out based on the analysis model used. The results of the analysis show that the factors that constrain people to move to Sharia banking are Fee Interest Factor, Information Factor, Location Factor, Relationship and Reputation Factor, Religiosity Factors, Product Factor, and Financial Risk Cost Factor. There are four findings of new factors as novelty of this study, namely Fee Interest Factors, Location Factors, Religiousity Factors, and Product Factors, as barriers to switch for the service industry, especially Sharia banking.